Formulating Integrated Public Services in Batu City: A Preliminary Study - Suhermanto, Dedik F; Roziqin, Ali; Sihidi, Iradhad T; Indrawan, Temmy; Rahmawati, Yusrin (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to develop an initial framework for integrating public services in Batu City. The integration of public services in Batu City is formulated into the Integrated Public Service (Public Service Mall). This research is preliminary, meaning that researchers wanted to identify potential public services developed in Batu City. Furthermore, the discussion of the initial framework focused on three aspects, namely institutional, management, and human resource management. This research used a mixed-methods approach. Furthermore, data collection was carried out through questionnaires, semi-structured interviews, focus group discussions, and literature studies. The results uncovered that the integration of public services in Batu City has the potential to be developed through Public Service Mall. The strategic placement of Public Service Mall locations is also needed to provide affordability for the community. Public Service Mall can also expand the types of services from 118-130 to 130-140. From an institutional perspective, Public Service Mall remains under the Batu City One-Stop Integrated Service and Investment Service (DPMPTSP) supervision by coordinating with technical agencies from the public and private sectors. Then, in terms of management, the implementation of the Public Service Mall requires physical and network infrastructure in the service process. Finally, the HRM (Human Resource Management) aspect needs to pay attention to the competency skills of the apparatus, both as implementers and control systems.